The Teaching Learning Process of Public Speaking from An Ethnographical Perspective - E. T. Karmala; Diah Kristina; Slamet Supriyadi (Universitas Jambi, Magister Program of English Education Department, 2019)
This research aims to explore how the application of public speaking at an English course in Pare, Kediri, East Java. This research was qualitative in the form of ethnography research. The research objective is from an ethnography study in an English course in Pare Kediri East Java. The subject from the research is the teacher and students from public speaking class at an English course in Pare, Kediri, East Java. The data obtained through interviews, observation, and document analysis. The findings of the implementation of public speaking at an English course in Pare, Kediri, East Java. This study shows that there are three methods which the speeches were impromptu speech in the placement test to select students. Introduction speech to describe their name or background and storytelling speech with different themes to express their ideas and knowledge. Further, in the beginning, class, the teacher gives the power words to motivate students. Moreover, the teacher stimulates the speaking skill of students with dialog in the forum; The teacher gives the evaluation of strengths and weakness from students’ speech one by one.